Development and validation of quasi-steady-state heat pump water heater model having stratified water tank and wrapped-tank condenser. (March 2018) - Shen, Bo; Nawaz, Kashif; Baxter, Van; Elatar, Ahmed
Highlights: Calibration method to match water stratification. Couple a detailed vapor compression system model with a stratified water tank. Simulate varied condenser heat distribution to water nodes. Abstract: Heat pump water heater systems (HPWH) introduce new challenges for design and modeling tools, because they require vapor compression system balanced with a water storage tank. In addition, a wrapped-tank condenser coil has strong coupling with a stratified water tank, which leads HPWH simulation to a transient process. To tackle these challenges and deliver an effective, hardware-based HPWH equipment design tool, a quasi-steady-state HPWH model was developed based on the DOE/ORNL Heat Pump Design Model (HPDM). Two new component models were added via this study. One is a one-dimensional stratified water tank model, an improvement to the open-source EnergyPlus water tank model, by introducing a calibration factor to account for bulk mixing effect due to water draws, circulations, etc. The other is a wrapped-tank condenser coil model, using a segment-to-segment modeling approach. The HPWH system model was validated against available experimental data. After that, the model was used for parametric simulations to determine the effects of various design factors.